Silenced witnesses: Israel is killing journalists in Gaza at historic rates - Walid El Houri (Global Voices, 2025)
As the toll mounts, so too does the sense of abandonment felt by Gaza’s journalists who continue to witness and report in the most difficult conditions.
Palestine (Permanent Observer to the UN)